2023
DOI: 10.1111/nph.18633
|View full text |Cite
|
Sign up to set email alerts
|

CIPK‐B is essential for salt stress signalling in Marchantia polymorpha

Abstract: Summary Calcium signalling is central to many plant processes, with families of calcium decoder proteins having expanded across the green lineage and redundancy existing between decoders. The liverwort Marchantia polymorpha has fast become a new model plant, but the calcium decoders that exist in this species remain unclear. We performed phylogenetic analyses to identify the calcineurin B‐like (CBL) and CBL‐interacting protein kinase (CIPK) network of M. polymorpha. We analysed CBL‐CIPK expression during sal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…CRISPR-Cas9 techniques enable the targeted manipulation of CBL or CIPK genes, enhancing their activity or modifying their regulatory properties. Tansley et al [39] created genetic knockouts in the liverwort Marchantia polymorpha, confirming the existence of two CIPKs and three CBLs. The study revealed significant salt-responsive transcriptional changes in both CIPKs and one CBL, allowing for improved precision in fine-tuning stress tolerance in crops.…”
Section: Implications For Crop Stress Resilience and Future Perspectivesmentioning
confidence: 90%
See 1 more Smart Citation
“…CRISPR-Cas9 techniques enable the targeted manipulation of CBL or CIPK genes, enhancing their activity or modifying their regulatory properties. Tansley et al [39] created genetic knockouts in the liverwort Marchantia polymorpha, confirming the existence of two CIPKs and three CBLs. The study revealed significant salt-responsive transcriptional changes in both CIPKs and one CBL, allowing for improved precision in fine-tuning stress tolerance in crops.…”
Section: Implications For Crop Stress Resilience and Future Perspectivesmentioning
confidence: 90%
“…These interactions likely participate in the coordination and modulation of salt stress signaling in the plant. Tansley et al [39] studied calcium decoder proteins in Marchantia polymorpha, finding protein-protein interactions among all CBL-CIPKs, and observed increased salt sensitivity upon knocking out CIPK-B, suggesting its role in salt signaling.…”
Section: The Regulation Of the Cbl-cipk Pathway By Gene Expression An...mentioning
confidence: 99%
“…For instance, CRISPR/Cas-mediated inactivation significantly enhanced grain weight in rice ( Oryza sativa ) by targeting OsGW5 (Liu et al, 2017) and OsMADS1 ( MADS-BOX TRANSCRIPTION FACTOR 1 ) (Wang et al, 2024), production of low-gluten wheat ( Triticum aestivum ) through editing the α-gliadin gene array (Sánchez-León et al, 2018), and powdery mildew resistance of tomato ( Solanum lycopersicum ) (Nekrasov et al, 2017). In the past decade, CRISPR/Cas technology has been successfully utilized to modify more than 130 green plant species based on a recent review (Cardi et al, 2023), including 110 angiosperms (mostly agricultural and horticultural crops with significant economic values) (Kis et al, 2019; Wang et al, 2023), and 7 gymnosperms (Ren et al, 2021; Ye et al, 2023), 3 mosses (Tansley et al, 2023; Tavernier et al, 2023; Yuan et al, 2023), and 12 algae (Belshaw et al, 2023; Patel et al, 2023; Zhang et al, 2023) without any species of ferns or lycophytes.…”
Section: Introductionmentioning
confidence: 99%